1979
DOI: 10.1677/joe.0.0820043
|View full text |Cite
|
Sign up to set email alerts
|

Foetal-Maternal Production and Transfer of Cortisol During the Last Days of Gestation in the Guinea-Pig

Abstract: The metabolism and the rate of transfer of cortisol across the placenta in pregnant guinea-pigs and foetuses were studied by constant intravenous infusions of tritium-labelled cortisol. Estimates of endogenous and radioactive plasma cortisol levels were used to calculate the following parameters at four stages before parturition (days 62, 64, 66 and 67; parturition occurring at day 68): metabolic clearance rate; production rate; adrenal secretory rate; transfer rate from mother to foetus and from foetus to mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
4
24
0
Order By: Relevance
“…High plasma PBG levels were associated with very low progesterone TCM during gestation (Illingworth et at., 1970). Similarly, high transcortin plasma levels paralleled a low cortisol TCM (3 times lower than in non-pregnant females) (Dalle and Delost, 1979).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…High plasma PBG levels were associated with very low progesterone TCM during gestation (Illingworth et at., 1970). Similarly, high transcortin plasma levels paralleled a low cortisol TCM (3 times lower than in non-pregnant females) (Dalle and Delost, 1979).…”
Section: Introductionmentioning
confidence: 82%
“…These high levels result from a regular rise in foetal plasma cortisol levels during the last days of gestation, which parallels the increase in maternal plasma and adrenal cortisol concentrations, foetal adrenal cortisol content increasing only during the last 24 hrs of gestation (Dalle and Delost, 1976). Recent studies (Dalle and Delost, 1979) Murphy (1967), modified as described previously (Dalle and Delost, 1976). Cortisol binding parameters were determined using the method of Pearlman and Crepy (1967), adapted for corticosteroids (Pradier, 1979 Free and bound cortisol levels in the foetus ( fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After palpation, laparotomy was performed just above the neck of 1 fetus to insert a polyethylene catheter (Bio trol No. 1) in one carotid artery [5,16].…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of adrenal secretion rates in acute experiments (Dalle and Delost, 1979) have shown that the maternal adrenals are the principal source of the cortisol found in both the maternal and the fetal pools.…”
Section: Introductionmentioning
confidence: 99%